2017
DOI: 10.1111/eip.12468
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the inpatient care of young adults experiencing early psychosis: A medical record review

Abstract: There is wide variation in the rate at which various clinical care processes are performed and in the provision of inpatient care to younger adults experiencing episodes of early psychosis. Consistent standards of care are needed to reduce variations and improve treatment outcomes and experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In adolescent units, the prevalence of restrictive interventions ranges from 6% to over 50% (Angold & Pickles, ; Baeza et al, ; Donovan et al, ; Furre et al, ; Swadi & Bobier, ). In Canada, it was found that 32% of young people aged less than 25 years experienced seclusion during their inpatient admission, however, less than 1% experienced restraint (Puyat et al, ). Furthermore, individuals admitted to hospital can often experience restrictive interventions during the process of being admitted, such as in Emergency Departments or by the police.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In adolescent units, the prevalence of restrictive interventions ranges from 6% to over 50% (Angold & Pickles, ; Baeza et al, ; Donovan et al, ; Furre et al, ; Swadi & Bobier, ). In Canada, it was found that 32% of young people aged less than 25 years experienced seclusion during their inpatient admission, however, less than 1% experienced restraint (Puyat et al, ). Furthermore, individuals admitted to hospital can often experience restrictive interventions during the process of being admitted, such as in Emergency Departments or by the police.…”
Section: Discussionmentioning
confidence: 99%
“…The Safewards intervention has been introduced onto the IPU, subsequent to the study period, and this intervention has been demonstrated to be effective in reducing the prevalence in restrictive interventions (Bowers et al, ). Second, a study conducted in Canada found that the use of restraint was higher in the emergency department compared to the ward (16% vs <1%) (Puyat et al, ) and unless this information is routinely collected, the actual rate of restrictive interventions will be grossly under‐estimated. However, this is complicated, as it would involve the routine collection of data from multiple different agencies or services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is crucial that they have positive experiences of inpatient care in order to reduce the risks of both traumatisation, and subsequent disengagement from mental health services. Nursing staff play a key role in ensuring the quality of that care (McDougall & Sanderson, 2016), but evidence suggests that acute care practices with young people may be poorly evidenced (Dusseldorp, Goossens & Achterberg, 2011), and are generally nonstandardised (Puyat et al, 2017). There is very little literature which provides evidence for best practice, however.…”
mentioning
confidence: 99%